Ecocene Politics. - Tănăsescu, Mihnea (Cambridge, UK : Open Book Publishers, 2022)
Anchored in the diverse ecological practices of communities in southern Italy and Aotearoa/New Zealand, this book devises a unique and considered theoretical response to the shortcomings of global politics in the Ecocene--a new temporal epoch characterised by the increasingly frequent intrusion of ecological processes into political life.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books